Age, sex, and breeding status shape a complex foraging pattern in an extremely long‐lived seabird. Issue 8 (1st August 2014) - Jaeger, Audrey; Goutte, Aurélie; Lecomte, Vincent J.; Richard, Pierre; Chastel, Olivier; Barbraud, Christophe; Weimerskirch, Henri; Cherel, Yves
Abstract : Evidence of age‐dependent changes in foraging behavior of free‐ranging individuals is scarce, especially at older stages. Using the isotopic niche as a proxy of the trophic niche during both the breeding (blood) and inter‐nesting (feather) periods, we report here empirical evidence for age‐, gender‐, and breeding status‐dependent foraging ecology and examine its potential consequences on subsequent reproduction and survival in an extremely long‐lived species, the Wandering Albatross ( Diomedea exulans ). Immature Wandering Albatrosses of both sexes forage in the subtropics (δ 13 C) and feed at the same trophic position (δ 15 N) as the adults. In contrast to immature birds, adult females forage, on average, at more northern latitudes than males, with both sexes feeding in the subtropics during the inter‐nesting period, and males, not females, favoring subantarctic waters during incubation. In contrast to adult females, males show a unique pattern among birds and mammals of a continuous change with age in their main feeding habitat by foraging progressively farther south in colder waters during both the breeding and inter‐nesting periods. In males, foraging at higher latitudes (lower feather δ 13 C values) is associated with a lower probability of breeding during the following years compared to other birds, but with no effect on their probability of surviving. Foraging in cold and windy waters may be linked to foraging impairment that might explain different life history trade‐offs and lower investment in reproduction with age. This key point requires further longitudinal investigations and/or studies examining foraging success and the energy budget of birds feeding in different water masses.